Pengaruh Penggunaan Media Aplikasi Canva Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Konsep Dasar IPS - Thesalonika, Emelda; Arent, Ease (Jurnal Simki Pedagogia, 2023)
The purpose of this research is to find out how much influence the use of Canva media has for PGSD students in taking the Basic Social Sciences Learning Concepts course. The type of research used is quantitative research with a quasi-experimental method. This research uses 2 classes, namely the experimental class, namely Canva learning media and the control class using Microsoft Power Point. The results of the research proved that the average pre-test score for the experimental class was 42.4 and for the control class was 41.2. The experimental results obtained tcount = 0.311 and ttable = 1.708 because tcount <ttable, the two samples had the same initial performance. The average post-test score for the experimental class was 76 with a standard deviation of 12.24 and for the control class was 67.6 with a standard deviation of 12.67. The results of the post-test scores for the research class and the control class were tested using a one-party t experiment and the results were 2.780 > 1.708, namely tcount > ttable at a significance level of 0.05 then (Ha) was accepted and Ho was rejected, which means that there is an effect of Canva media on learning outcomes students on the material influence of Western/foreign culture in Indonesia.